Hypoxia in Breast Cancer—Scientific Translation to Therapeutic and Diagnostic Clinical Applications - Zhang, Ying; Zhang, Hongyi; Wang, Minghong; Schmid, Thomas; Xin, Zhaochen; Kozhuharova, Lora; Yu, Wai-Kin; Huang, Yuan; Cai, Fengfeng; Biskup, Ewelina (Frontiers in Oncology, 2021)
Breast cancer has been the leading cause of female cancer deaths for decades. Intratumoral hypoxia, mainly caused by structural and functional abnormalities in microvasculature, is often associated with a more aggressive phenotype, increased risk of metastasis and resistance to anti-malignancy treatments. The response of cancer cells to hypoxia is ascribed to hypoxia-inducible factors (HIFs) that activate the transcription of a large battery of genes encoding proteins promoting primary tumor vascularization and growth, stromal cell recruitment, extracellular matrix remodeling, cell motility, local tissue invasion, metastasis and maintenance of the cancer stem cell properties. In this review, we summarized the role of hypoxia specifically in breast cancer, discuss the prognostic and predictive value of hypoxia factors, potential links of hypoxia and endocrine resistance, cancer hypoxia measurements, further involved mechanisms, clinical application of hypoxia-related treatments and open questions.